Discretion of Covid 19 Prevention in the Perspective of State Administrative Law - Mohamad Khamim; Moh Taufik (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Strategic steps in handling the Covid 19 pandemic have been made by the Regional government to accelerate the handling of Covid-19. This study aims to look at the position of discretion as an instrument of administrative law in the formation of public policy, and analyze the extent to which discretion is used by regional heads as an effort to make effective policies in preventing covid 19 in their regions as part of the bureaucratic agility paradigm. This research uses an empirical juridical approach, with the data analysis method being carried out by collecting data through the study of library materials or secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials, both in the form of documents and applicable laws and regulations relating to normative juridical analysis of the synchronization of the Government Administration Law. The policy of handling covid 19 carried out by several regions has succeeded in reducing the mortality rate through discretion, with a more flexible and flexible policy character in carrying out the role of responsive bureaucratic agility. The approach of State Administration law provides more legal certainty and avoids clashes of constitutional issues in realizing public welfare and justice.Keywords: Discretion, Covid 19 Prevention, State Administrative Law